Binge‐eating disorder is associated with an unfavorable body mass composition in patients with non‐alcoholic fatty liver disease. Issue 11 (17th July 2021) - Forlano, Roberta; Harlow, Christopher; Mullish, Benjamin H.; Thursz, Mark R.; Manousou, Pinelopi; Yee, Michael
Abstract: The interaction between eating disorders and non‐alcoholic fatty liver disease (NAFLD) remains unexplored, especially with regards to binge‐eating disorder (BED). Our team conducted a service evaluation project in order to assess risk factors for the presence of BED among patients with NAFLD and the impact of BED on body mass composition. The overall prevalence of patients screening positive to BED Screener‐7 (BEDS‐7) was 28.4%, while a previous diagnosis of depression and marital status (as single or separated) were independently associated with positive BED. Furthermore, patients with positive BEDS‐7 had higher BMI, with greater visceral component and overall lower muscle mass. There was no difference in terms of liver disease severity as assessed by noninvasive markers of fibrosis. However, as body mass composition and sarcopenia have been shown to be associated to disease progression in patients with NAFLD, further studies are required to ascertain the long‐term impact of BED in these patients. Moreover, further work is warranted to identify to implement multidisciplinary approach within clinical psychology for the management of patients with BED, who may be particularly challenging in terms of achieving lifestyle modifications. As a hepatology community, we should address NAFLD with a more holistic approach. Abstract :